SCREENING GENETIC VARIABILITY IN ADVANCE LINES FOR DROUGHT TOLERANCE OF BREAD WHEAT (TRITICUM AESTIVUM) - ARYA, SANTOSH; D. K. MISHRA; S. S. BORNARE (The Bioscan, 2013)
Screening of 54 advanced lines of wheat including three checks viz., MP-3173 (C), MP-3020 (C) and HI-8427 (C) was carried out under rainfed sown condition with objectives to estimate genetic variability for various traits to identify potential genotypes for drought tolerance. All the advance lines of wheat studied in investigation revealed considerable amount of genetic variability for majority of the traits. Grain yield per plant showed significant positive correlation with number of tillers per plant (rp = 0.752), biological yield per plant (rp = 0.703), root biomass (rp = 0.651), root length per plant (rp = 0.521), days to maturity (rp = 0.369) spike length (rp = 0.290), harvest index (rp = 0.200), spike density (rp = 0.192), thickness of stem (rp = 0.187) and 1000- grain weight (rp = 0.165). Path analysis indicated that biological yield per plant (1.017) followed by harvest index (0.740) and number of spikelet per spike (0.206) were the main yield contributing traits suggesting the possibility of improving grain yield through direct selection of these traits. It is suggested that, these characters can be considered as selection criteria in improving the grain yield of durum wheat genotypes. On account of this genetic variability it has been found that genotypes JWJ-4, JWJ-7, JWJ-52, JWJ-34, JWJ-37, JWJ-26, JWJ-19, JWJ-38 and JWJ-18 were potential genotypes.